Bacillus amyloliquefaciens- modified clay for controlling harmful algal blooms in eutrophic aquaculture ponds - Wu, Zaixing; Yu, Zhiming; Song, Xiuxian; Jiang, Kaiqin; Cao, Xihua; Yuan, Yongquan (Frontiers in Microbiology, 2025)
IntroductionBacillus amyloliquefaciens is a commonly used probiotic microecological regulator in aquaculture water with the ability to inhibit harmful algae blooms (HABs) and improve the health status of aquaculture ecosystem. Modified clay has been widely applied in the field for eliminating HABs.MethodsIn this study, clay particles are used as carriers and to provide a microenvironment for microbial fermentation, yielding a microbial modified clay product with high efficiency for eliminating typical HAB organisms. Methods are developed for the fermentation of microorganisms and clay particles and also for subsequent preparation of a dry powder, which stably produce microbial modified clay in dry powder form for HAB elimination.ResultsThe results showed that the obtained microbial modified clay has a stable bacterial content of more than 109 cfu/mL, and the removal rate of the HAB organism Heterosigma akashiwo equivalent to that obtained with other HAB removal materials at the same dosage, indicating good potential for HAB removal. The removal rate of Heterosigma akashiwo at a dosage of 0.1 g/L microbial modified clay exceeded 90%.DiscussionBy combining two natural and commonly used material, both the function of emergency flocculation disposal (when HAB outbreaks) and long-term ecological regulation (to maintain a healthier phytoplankton community structure through specific algicidal effect) were achieved, resulting in a 1 + 1 > 2 effect when applied in the eutrophic aquaculture environment. Also, this exploratory study with the unique combination of microbial fermentation and clay modification preliminarily provides an important scientific basis for promoting the large-scale application of microbial modified clay in the field of HAB control, especially in the eutrophic aquaculture ecosystems. Also, extensive ecological assessment before field application is still required, such like the scientific support of environmental criteria, the safety to other aquaculture organisms and the ecological effect of the whole aquaculture ecosystem.